Ten Good Reasons to Practice Neuroultrasound in Critical Care Setting - Bittencourt Rynkowski, Carla; Caldas, Juliana (Frontiers in Neurology, 2022)
At the beginning, cerebral ultrasound was not considered feasible because the intact skull was a seemingly impenetrable obstacle. For this reason, obtaining a clear image resolution had been a challenge since the first use of transcranial ultrasound (TCU) for the assessment of small deep brain structures. However, the improvements in transducer technologies and advances in signal processing have refined the image resolution and the role of TCU has evolved as an imaging modality for the brain parenchyma within multiple pathologies. This paper summarizes ten crucial applications of cerebral ultrasonography for the evaluation and management of neurocritical patients, whose transfer from and to intensive care units poses a real problem to medical care staff. This also encompasses ease of use, low cost, wide acceptance by patients, no radiation risk and relative independence from movement artifacts. Bedside availability and reliability raised the interest of critical care intensivists in using it with  increasing frequency.  In this mini review, the usefulness and the advantages of ultrasound in the neurocritical care setting are discussed regarding ten aspects.